LANDEK DALAM UPACARA ADAT NGAMPEKEN TULAN-TULAN KAJIAN INTERAKSI SIMBOLIK PADA MASYARAKAT KARO DI DESA RUMAMIS KECAMATAN BARUS JAHE KABUPATEN KARO - Nadra Akbar Manalu Akbar Manalu (Gesture: Jurnal Seni Tari, 2013)
The aim of this writing is to descript the presentation of landek, to descript the symbolic interaction, and to descript landek symbol in Ngampeken Tulan-tulan tradition ceremony of Karo society.the research was carried out for 3 months, from june 2013 to august 2013. the place of research is in rumanis village barus jahe subdistrict Karo regency. Ngampeken tulan tulan tradition ceremony is raise bone, a tradition ceremony that still doing by karo society for give the last respect to parents who had died or built Geriten (monument or special building to saving cranium) landek in ngampeken tulan tulan ceremony have a part to deliver meaning in the process of traditon ceremony with a simple dancing and to deliver family's sorrow to be patient and not to deep in sadness. there is symbolic interaction in ngampeken tulan tulan tradition ceremony that shown on dancing (landek) in family of karo society named rakut sitelu. rakut sitelu have duty and responsibility based on tradition. landek symbol as a deliver meaning in ngampeken tulan tulan tradition ceremony. where sukut, kalimbubu, anak beru is dancing followed music and lyrics (pengapul) from perkolong-kolong